2009
DOI: 10.1111/j.1745-4549.2008.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Adsorption Behavior of Biscuits Formulated Using Wheat, Oatmeal and Passion Fruit Flour

Abstract: Moisture adsorption isotherms from a new biscuit considered as functional food were determined using a gravimetric static method at 25 and 40C and over a range of relative humidity from 0.112 to 0.903. The biscuit had 2.5, 3.3, 10.0 and 31.0% of ash, fiber, protein and fat, respectively, and 4.7% moisture content. The equilibrium moisture content of the biscuit (kg/kg) increased when the storage temperature at any given water activity (Aw) was reduced. The experimental data were analyzed using different models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
(28 reference statements)
1
15
0
4
Order By: Relevance
“…Guillard et al (2004) reported that dry biscuit exhibited Type III behaviour, with an uptake of moisture of 10 g/100 g (wet basis, wb) at 0.70 a w increasing significantly above this value to 34 g/100 g (wb) at 0.97 a w . Similar Type III curve was observed by Sampaio et al (2009) in a composite flour biscuits made from wheat, oatmeal and passion fruits flour. It was reported that the equilibrium moisture content increased steeply above 0.70 a w .…”
Section: Moisture Adsorption Isothermssupporting
confidence: 81%
See 2 more Smart Citations
“…Guillard et al (2004) reported that dry biscuit exhibited Type III behaviour, with an uptake of moisture of 10 g/100 g (wet basis, wb) at 0.70 a w increasing significantly above this value to 34 g/100 g (wb) at 0.97 a w . Similar Type III curve was observed by Sampaio et al (2009) in a composite flour biscuits made from wheat, oatmeal and passion fruits flour. It was reported that the equilibrium moisture content increased steeply above 0.70 a w .…”
Section: Moisture Adsorption Isothermssupporting
confidence: 81%
“…However, the goodness-of-fit was poor for Ferro-Fontan and GAB models in terms of P and RMS%. Sampaio et al (2009) reported that GAB model was found to be most suitable for describing the adsorption characteristics of composite flour biscuit containing wheat, oatmeal and passion fruit flour. Palou et al (1997) reported that Peleg and GAB equations adequately predicted the isotherms of cookies with mean relative deviation less than 7 %.…”
Section: Sorption Models and Associated Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is present in virtually all foods, and it is important for a number of chemical. Moisture determination is one of the most common tests in foods since the water content in foods has an important relationship between conservation and the chemical, physical and microbiological changes during the storage (SAMPAIO et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Após terem suas umidades determinadas e relacionadas com as atividades de água correspondentes, as isotermas de adsorção foram ajustadas matematicamente, empregando análise de regressão não-linear, com o auxílio do Origin 8.0. De acordo com a Tabela 2, foram testados cinco modelos largamente empregados na literatura para determinação de isotermas de alimentos: Brunauer, Emmett e Teller (BET), Gugghenheim, Anderson e de Boer (GAB), Oswin, Henderson e Peleg (Sampaio et al, 2009 …”
Section: Methodsunclassified